THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE AND FINANCIAL MANAGEMENT ON INTEREST IN STARTING A BUSINESS IN STUDENTS OF FEBI IAIN KERINCI - Kartika, Vhyola Dewi; Mailindra, Wiyan; Sumanti, Eva (Asian Journal of Islamic Economic Studies, 2024)
This study aims to determine the effect of Entrepreneurial Knowledge of Entrepreneurship and Financial Management, simultaneously or partially, on the interest in starting a business for students of the Islamic Economics and Business Faculty IAIN Kerinci. This type of research is descriptive quantitative research. The population in this study were students of the Faculty of Economics and Islamic Business IAIN Kerinci majoring in Islamic Banking and Islamic Economics class of 2018 and 2019. The sample was determined using a cluster random sampling technique so that the respondents of this study were 82 students. Data collection techniques using a questionnaire. The data analysis technique in this study uses multiple linear regression analysis with the help of the program SPSS version 23. The results showed that both partially and simultaneously entrepreneurial knowledge of entrepreneurship and financial management significantly affected the interest in starting a business for students of the Faculty of Economics and Islamic Business IAIN Kerinci.